2017
DOI: 10.1038/s41467-017-01890-w
|View full text |Cite
|
Sign up to set email alerts
|

Alu-dependent RNA editing of GLI1 promotes malignant regeneration in multiple myeloma

Abstract: Despite novel therapies, relapse of multiple myeloma (MM) is virtually inevitable. Amplification of chromosome 1q, which harbors the inflammation-responsive RNA editase adenosine deaminase acting on RNA (ADAR)1 gene, occurs in 30–50% of MM patients and portends a poor prognosis. Since adenosine-to-inosine RNA editing has recently emerged as a driver of cancer progression, genomic amplification combined with inflammatory cytokine activation of ADAR1 could stimulate MM progression and therapeutic resistance. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 44 publications
3
120
0
Order By: Relevance
“…These findings might suggest that RNA editing of GLI1 can have a negative impact on GLI1-dependent tumorigenesis. However, it was recently shown that GLI1 editing is associated with multiple myeloma development, highlighting the context-specific impact of this GLI1 post-transcriptional modification in tumor biology and suggesting that additional investigation into this complex phenomenon is required (Lazzari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These findings might suggest that RNA editing of GLI1 can have a negative impact on GLI1-dependent tumorigenesis. However, it was recently shown that GLI1 editing is associated with multiple myeloma development, highlighting the context-specific impact of this GLI1 post-transcriptional modification in tumor biology and suggesting that additional investigation into this complex phenomenon is required (Lazzari et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Several other papers published after 2014 [42, 43] also suggested some role for PTEN in glaucoma. MeTeOR also predicted an association between GLI1 and multiple myeloma, and in 2017, Alu-dependent RNA editing of GLI1 was shown to promote malignant regeneration in multiple myeloma [44].…”
Section: Resultsmentioning
confidence: 99%
“…In vivo studies showed that leukemia progenitor cells harboring this misspliced GSK3β gene displayed enhanced β-catenin expression, which was required for the self-renewal of leukemia stem cells (LSCs) [50]. It was estimated that the genomic amplification of ADAR1 occurred in 30-50% of multiple myeloma patients and portended an unfavorable prognosis [51]. The silencing of ADAR1 attenuated in vivo engraftment of myeloma through suppression of the transcriptional activity of GLI1 [51], a self-renewal agonist and candidate marker for CSCs [64].…”
Section: A-to-i Modification and Cancer Stem Cellsmentioning
confidence: 99%
“…It was estimated that the genomic amplification of ADAR1 occurred in 30-50% of multiple myeloma patients and portended an unfavorable prognosis [51]. The silencing of ADAR1 attenuated in vivo engraftment of myeloma through suppression of the transcriptional activity of GLI1 [51], a self-renewal agonist and candidate marker for CSCs [64]. Further studies have shown that ADAR1 can edit exon 12 of the GLI1 transcript, leading to a novel GLI1 protein with a point mutation ( Fig.…”
Section: A-to-i Modification and Cancer Stem Cellsmentioning
confidence: 99%